2020
DOI: 10.1016/s2468-2667(20)30117-1
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-hospital cardiac arrest during the COVID-19 pandemic in Paris, France: a population-based, observational study

Abstract: Background Although mortality due to COVID-19 is, for the most part, robustly tracked, its indirect effect at the population level through lockdown, lifestyle changes, and reorganisation of health-care systems has not been evaluated. We aimed to assess the incidence and outcomes of out-of-hospital cardiac arrest (OHCA) in an urban region during the pandemic, compared with non-pandemic periods. MethodsWe did a population-based, observational study using data for non-traumatic OHCA (N=30 768), systematically col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

39
450
6
21

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 431 publications
(516 citation statements)
references
References 22 publications
39
450
6
21
Order By: Relevance
“…1-2). OHCAs during the COVID-19 pandemic were more likely to occur at home in Italy (90% during the pandemic vs. 83% in the non-pandemic period; P = 0.005) 6 and France (90% vs. 77%; P < 0.001) 7 while in the other studies were similar 9 , 10 , 23 (Supplemental Fig. 3).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…1-2). OHCAs during the COVID-19 pandemic were more likely to occur at home in Italy (90% during the pandemic vs. 83% in the non-pandemic period; P = 0.005) 6 and France (90% vs. 77%; P < 0.001) 7 while in the other studies were similar 9 , 10 , 23 (Supplemental Fig. 3).…”
Section: Resultsmentioning
confidence: 76%
“…Survival at hospital discharge was reported in three studies 6 , 7 , 23 and survival with good neurologic outcome only in one. 23 In France, patients suffering an OHCA during the COVID-19 pandemic were less likely to survive: rates of survival at hospital discharge declined from 5.4% to 3.1% ( P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marijon et al reported that the over a period of 4.5 weeks, weekly OHCA incidence doubled to 26.64 from 13.42, per million inhabitants, in the beginning of pandemic, before returning to baseline. 8 The increase in OHCAs was mostly due to 30% increase in COVID-19 cases. Marijon et al speculated that poor outcomes were caused by lockdown, behavior changes in bystanders, and an overwhelmed EMS.…”
Section: Introductionmentioning
confidence: 96%
“…The reports from China, France, and Italy suggest that outcomes of COVID-19 patients, who suffer either inhospital or out-of-hospital arrest, are poor. 5 8 Since many components of CPR generate aerosol, the WHO has listed CPR as an aerosol-generating procedure (AGP). 9 Infected HCWs pose a “triple threat” in current circumstances, loss of a HCWs to, and addition of a new patient (the HCW) to the overburdened healthcare systems, and a source of infection to coworkers and community.…”
Section: Introductionmentioning
confidence: 99%